Advancing metabolic networks and mapping updated urinary metabolic fingerprints after exposure to typical carcinogenic heterocyclic aromatic amines. (15th February 2023) - Zhu, Li; Jia, Wei; Wan, Xuzhi; Zhuang, Pan; Ma, Guicen; Jiao, Jingjing; Zhang, Yu
Abstract: Heterocyclic aromatic amines (HAAs) were not only present in cooked foods and cigarette smoke, but also measured in airborne particles and diesel-exhaust particles. Typical HAAs have been reported to induce carcinogenicity and metabolic disturbances, but how these hazardous compounds interfere with metabolic networks by regulating metabolic pathways and fingerprinting signature metabolites as biomarkers remains ambiguous. We developed an advanced strategy that adopted chemical isotope labeling ultrahigh-performance liquid chromatography coupled to quadrupole-Orbitrap high-resolution mass spectrometry for urinary nontargeted metabolomics analysis to gain new insight into in vivo physiological responses stimulated by exposure to typical HAAs. Rats were orally administered with a single dose of 2-amino-1-methyl-6-phenylimidazo[4, 5- b ]pyridine (PhIP) or 2-amino-3, 8-dimethylimidazo[4, 5- f ]quinoxaline (MeIQx) (1 and 10 mg/kg bw) and their D3 -isotopic compounds, respectively, and urine samples were then continuously collected within 36 h. Metabolomics data were acquired and processed by classical multivariate statistical analysis, while urinary metabolites were further identified and characterized according to mass spectrometric fragmentation rules, time- and dose-dependent profiles, and calibration of synthesized standards. We monitored 23 and 37 urinary metabolites as the biotransformation products of PhIP and MeIQx, respectively, and first identified demethylated metabolites of PhIP, tentatively named 2-amino-6-phenylimidazo[4, 5- b ]pyridine, and dihydroxylation products of classical HAAs as short-term biomarkers of exposure to further unravel the metabolic networks. In addition, our findings revealed that both HAAs significantly disturb histidine metabolism, arginine and proline metabolism, tryptophan metabolism, pyrimidine metabolism, tricarboxylic acid cycle, etc. Furthermore, we found that histamine, methionine, alanine, and 4-guanidinobutanoic acid could be considered potential characteristic biomarkers for the oncogenicity or carcinogenicity of both PhIP and MeIQx and screened their specific key pivotal metabolites. The current metabolomics approach is applicable in mapping updated urinary metabolic fingerprints and identifying potential specific biomarkers for HAAs-induced early tumorigenesis. Graphical abstract: Image 1 Highlights: We firstly identified N 1 -demethylated biotransformation products of PhIP. We provided updated evidence for unraveling metabolic networks of HAAs in vivo. We innovatively mapped urinary metabolic fingerprints from the exposure to HAAs. We discovered amino acid metabolic pathways significantly affected by HAAs. Potential characteristic biomarkers for the carcinogenicity of HAAs were screened.